Redefinition of arterial hypertension and considerations in pregnant women and in preeclampsia: Introduction to the symposium - Pacheco-Romero, José (2018)
In November 2017, various societies of the United States led by the American College of Cardiology and the American Association of Hypertension published a new joint Guideline on the Prevention, Detection, Evaluation, and Management of Arterial Hypertension in Adults. The Guideline determined new categories of blood pressure (BP) in adults: Normal < 120 / < 80 mm Hg, elevated blood pressure 120-129 / < 80 mm Hg, stage 1 hypertension 130-139/80-89 mm Hg and stage 2 hypertension > 140 / > 90 mm Hg. Interested in the opinion of experts, we asked their point of view regarding the implications these lower threshold values would have in the general adult population, in pregnant women and in pregnant women with preeclampsia.